(untitled) (Journal of Social Sciences Review, 2021)
The overall purpose of the study was to analyze and explore physical, verbal and social bullying in secondary schools of Khyber Pakhtunkhwa. The target population was all the principals, teachers and students, both male and female. The sample was selected through random stratified sampling techniques. A sample of 1800, (30 principals, 270 teachers and 1500 students) were selected from Charsadda, Mardan Nowshera, Peshawar, Malakand and Swabi. Five (four boys and one girl), secondary schools were randomly selected from each selected district. From each district five (05) principals, forty five (45) teachers and two hundred and fifty (250) students participated in the study. To achieve the objectives of the study, three questionnaires containing same items, were prepared one each for principals, teachers and students. The data was collected, tabulated, analyzed and interpreted by using Chi Square method. after analyzing the data it was concluded that students are made the victim of physical, verbal and social bullying in the Secondary Schools of Khyber Pakhtunkhwa